Analisis Pengaruh Komunikasi Tenaga Kesehatan Terhadap Kepuasan Pasien Rawat Jalan Di Klinik Pratama Siti Rahmah Tanjung Morawa - Chatrine Virginia Tamara; Tri Niswati Utami; Nur Aini - (Jurnal Kesmas Prima Indonesia, 2021)
Satisfaction is an important thing in improving services to the patients. The patient will feel satisfied if the service is acceptable according to the standard or in excess of that expected. The purpose of this study was to analyze the influence communication of health workers to the satisfaction of outpatients. This type of research was a quantitative with cross sectional design. Research carried out in the Pratama Clinical of Siti Rahmah in Tanjung Morawa. The study population of 130 people, and a sample of 98 respondents. A sampling technique that is purpose sampling. Data analysis for univariate, bivariate using simple linear regression at 95% confidence level. The results showed that the communication of health worker was, and outpatients feel satisfied but the service of the hospital was still far from the minimum service standards of the hospital. Communication health workers affect patient satisfaction in the outpatient Pratama Clinical of Siti Rahmah with medium strength and the direction is positive, which means if communication health workers increases, the satisfaction of outpatients also increased. Conclusion this study that the better the communication of health workers on an outpatient basis it will further improve patient satisfaction with outpatient care. The Clinic need to create a questionnaire, the level of satisfaction of patients and evaluated routinely to find out the extent of the level of satisfaction felt by the patient after getting the service.